2017
DOI: 10.1016/j.jconrel.2017.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Cationic microbubbles and antibiotic-free miniplasmid for sustained ultrasound–mediated transgene expression in liver

Abstract: Despite the increasing number of clinical trials in gene therapy, no ideal methods still allow non-viral gene transfer in deep tissues such as the liver. We were interested in ultrasound (US)-mediated gene delivery to provide long term liver expression. For this purpose, new positively charged microbubbles were designed and complexed with pFAR4, a highly efficient small length miniplasmid DNA devoid of antibiotic resistance sequence. Sonoporation parameters, such as insonation time, acoustic pressure and durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 39 publications
0
32
1
Order By: Relevance
“…The low P max− and the high frequency components of the PA waves used in this work place their mechanical index below the onset of cavitation, MI = P max− /√ f < 0.7, where the pressure is in MPa and the frequency in MHz 36 . This contrasts with sonophoresis ( f < 1 MHz) where the cavitation of microbubbles is responsible for transfection 37 or dermal delivery 38 . On the other hand, the high frequencies and high P max+ of PA waves lead to high stress gradients and high impulses that enable less common mechanisms of interaction between US and cells.…”
Section: Discussionmentioning
confidence: 95%
“…The low P max− and the high frequency components of the PA waves used in this work place their mechanical index below the onset of cavitation, MI = P max− /√ f < 0.7, where the pressure is in MPa and the frequency in MHz 36 . This contrasts with sonophoresis ( f < 1 MHz) where the cavitation of microbubbles is responsible for transfection 37 or dermal delivery 38 . On the other hand, the high frequencies and high P max+ of PA waves lead to high stress gradients and high impulses that enable less common mechanisms of interaction between US and cells.…”
Section: Discussionmentioning
confidence: 95%
“…This study confirmed how the optimization of ultrasound parameters and of the chemical and electrostatic structure of the microbubbles could play a pivotal role in increasing the efficacy of gene delivery. Moreover, the sonoporation method by Sonovue has already provided encouraging results in a recent human trial, whereas the gemcitabine treatment in inoperable pancreas cancer has been improved, extending the survival of patients without additional toxicity [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, no effect of in vivo transfection could be obtained with a low amount of DNA, which usually requires µg of plasmid. Here, we ought to use a small plasmid that already showed its ability to transfect the liver after a single injection of positively charged microbubbles in vivo [ 41 ].…”
Section: Resultsmentioning
confidence: 99%